Conformity Of the Content of The Spatial Pattern Plan of The RTRW of Tanjungbalai City with The Rtrw of North Sumatra Province - Indri Meiyanti; Abdi Sugiarto (Journal of Information Technology, computer science and Electrical Engineering, 2024)
The suitability of spatial pattern plans between Provincial RTRWs and City/Regency RTRWs is very important to ensure coordinated, sustainable, and efficient spatial management. This alignment supports harmonious development policies, prevents land use conflicts, and optimizes the use of natural resources and infrastructure. In addition, this conformity helps control development to fit the long-term vision, improve disaster risk mitigation, and create certainty for investment, resulting in safer and more targeted spatial planning at various levels of government. Fundamental problems and conflicts in space utilization arise due to significant challenges caused by overlapping policies, regulations, and geospatial information. The location of the study is in Tanjungbalai City which analyzes the comparison of the City Spatial Pattern Plan with the Provincial Spatial Pattern Plan. The provincial spatial pattern plan used is the 2023 Revision of the North Sumatra Provincial RTRW, while the urban spatial pattern plan uses the 2023 Tanjungbalai City RTRW Revision. This study aims to provide an overview of the evaluation of the non-conformity of the Tanjungbalai City Revised spatial pattern plan to the Revision of the RTRW of North Sumatra Province and provide steps to resolve the non-conformities that occur that are useful as material for discussion and evaluation of the Revised RTRW of Tanjungbalai City at the Provincial level..